Midwives' experiences of implementing respectful maternity care knowledge in daily maternity care practices after participating in a four-day RMC training - Veronica Millicent Dzomeku; Adwoa Bemah Boamah Mensah; Emmanuel Kweku Nakua; Pascal Agbadi; Jody R. Lori; Peter Donkor (BMC, 2021)
Abstract Background In Ghana, studies documenting the effectiveness of evidence-based specialized training programs to promote respectful maternity care (RMC) practices in healthcare facilities are few. Thus, we designed a four-day RMC training workshop and piloted it with selected midwives of a tertiary healthcare facility in Kumasi, Ghana. The present paper evaluated the impact of the training by exploring midwives' experiences of implementing RMC knowledge in their daily maternity care practices 4 months after the training workshop. Methods Through a descriptive qualitative research design, we followed-up and conducted 14 in-depth interviews with participants of the RMC training, exploring their experiences of applying the acquired RMC knowledge in their daily maternity care practices. Data were managed and analysed using NVivo 12. Codes were collapsed into subthemes and assigned to three major predetermined themes. Results The findings have been broadly categorized into three themes: experiences of practising RMC in daily maternity care, health facility barriers to practising RMC, and recommendations for improving RMC practices. The midwives mentioned that applying the newly acquired RMC knowledge has positively improved their relationship with childbearing women, assisted them to effectively communicate with the women, and position them to recognize the autonomy of childbearing women. Despite the positive influence of the training on clinical practice, the midwives said the policy and the built environment in the hospital does not support the exploration of alternative birthing positions. Also, the hospital lacked the required logistics to ensure privacy for multiple childbearing women in the open labour ward. The midwives recommended that logistics for alternative birthing positions and privacy in the ward should be provided. Also, all midwives and staff of the hospital should be taken through the RMC training program to encourage good practice. Conclusion Despite the report of some RMC implementation challenges, the midwives noted that the 4-day RMC training has had a positive impact on their maternity caregiving practice in the hospital. Policies and programs aimed at addressing the issue of disrespect and abusive practices during maternity care should advocate and include the building of facilities that support alternative birthing positions and privacy of childbearing women during childbirth.